Are Sales Successful Due to Salespeople Expertise and Adaptability? Gender and Age Dynamics in Investment Banking - Leslier Valenzuela-Fernández; Francisco Villegas Pinuer (SAGE Open)
This study provides valuable insights into understanding how salesperson behavior, whether technical knowledge (TK) or adaptive selling behavior (ASB), influences a customer’s attitude toward the salesperson (AS). We analyzed the relationships between investment bank customers and the bank in Chile using a cross-sectional sample of 115 customers. Multi-group structural equation modeling (SEM) analyses were performed to test the moderating effects of customer gender and age. The empirical analysis shows that a salesperson’s TK and ASB contribute significantly and positively to AS. Furthermore, there’s a synergistic effect between these two independent factors, indicating a reinforcement effect. The effect of TK on AS is significant for both males and females. In this line, no studies have jointly analyzed the effects of TK and ASB on AS from the customer perspective. About the moderation analysis, this pioneering article finds (1) moderating effects of age in the relationship between TK and AS in magnitude and between ASB and AS, which is significant only in the older customer groups (>50 years), and (2) moderating effects of gender in the relationship between ASB and AS, where it is only significant in female customers that consider relevant the adaptability in the investment context. These results reveal the relevance of aligning salespeople and customer demographic patterns. Therefore, these findings have critical implications for investment banking in developing sales strategies and cultivating customer relationships.